Taught not caught: exploring male adolescent experiences of explicitly transferring life skills from the sports hall into the classroom. Issue 2 (15th March 2019) - Allen, Georgia; Rhind, Daniel
ABSTRACT: Using sport domains to teach young people a wide range of life skills is not new, however there has been a recent emergence of research on life skills transfer, particularly from a sport environment into other life domains (e.g. school or work). As research in this field is still in its infancy, how younger adolescents effectively learn life skills or transfer skills into other life domains is still not fully understood. Therefore, the purpose of this study was to examine the life skill learning and transfer experiences of 20 male participants (12–13 years of age) in a school context. The Transfer-Ability Programme (TAP) was delivered in a state funded secondary school in London, UK, where the participants attended the programme directly after teaching hours, once weekly, for one academic year. The programme was a multi-faceted intervention, which sought to explicitly teach male participants life skills through sporting activities and facilitate transfer opportunities. Semi-structured interviews were conducted with 18 participants, one parent and one teacher at the end of programme and analysed using a thematic approach. Findings suggest that the use of explicit strategies and group discussions aid the learning and transfer of life skills. However, school-based, life skills programmes of a similar nature should consider increasing participant autonomy during the programme development stage in order to maximise the personal value and relevance placed on the life skills. Partnerships across the whole school environment also need to be evident in order to provide frequent opportunities for skill transfer.